Analysis of emergency peripartum hysterectomy in Northern Tasmania. (October 2014) - Lim, Wei How; Pavlov, Toly; Dennis, Amanda E.
Abstract Objective There is a need for emerging Australian data on emergency peripartum hysterectomy (EPH) especially in rural areas due to the associated high maternal morbidity and mortality. The aim of this study is to review the incidence and complications of EPH in the northern region of Tasmania. Design A retrospective cohort study at a single health care institution during a 10 year period. Setting Launceston General Hospital, the main maternity referral centre for the northern region of Tasmania. Participants Case notes of women coded with hysterectomy during childbirth were included and analysed. Main outcome measures Primary outcomes were maternal and neonatal morbidity and mortality. Results Eighteen women were identified, giving an incidence of 1.01 per 1000 births. Indications for surgery were abnormal placentation, uterine atony and uterine rupture. Maternal morbidity was high, and included intensive care admissions (55%), disseminated intravascular coagulopathy (50%), hypovolemic shock (38%), febrile illness (27%) and urinary tract injuries (22%). The mean estimated total blood loss was 4091.6 mL, and 88% of women received blood transfusions. All women received prophylactic antibiotics. Women with morbidly adherent placenta were likely to experience more complications and transfusions. There were no maternal or neonatal deaths identified. Conclusion The rate of peripartum hysterectomy in rural Tasmania is higher compared with other Australian tertiary‐level hospitals, suggesting that Australian women birthing in rural and regional areas might be at greater risk. Maternal morbidity associated with abnormal placentation is high; hence, better diagnostic modalities and multidisciplinary antenatal management are required to improve maternal outcomes.